Effects of Six Weeks of Modified and Standard Nordic Hamstring Exercises on Electromyography of Hamstring, Hip And Trunk Muscles and Sprint Performance in Young Male Football Players - Milad Farahbakhsh; Abdolhamid Daneshjoo; Mansour Sahebozamani; Rohollah Nikooie (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims hamstring injury is the most common injury in football. Nordic hamstring exercise (NHE) is one of the best hamstring injury prevention strategies. This study was aims to compare the effect of six weeks of standard NHE and modified NHE on electromyography of hamstring, hip and trunk muscles and sprint performance in young male football playersMethods In this study, participants were 26 male football players in Kerman, Iran who were selected using purposeful and convenience sampling methods and randomly divided into two groups of NHE (Age: 16.31±0.51 years, Height: 173.08±5.15 cm, weight: 59.85±5.71 kg) and modified NHE (Age: 16.41±0.54 years, Height: 173±6.84 cm, weigh: 64.20±8.76 kg). Sprint performance was measured by the 20-meter sprint test, and muscles activity was measured by electromyography. Repeated-measure analysis of variance was used for data analysis.Results In the modified NHE group, there was a significant difference between the pretest and posttest phases in the electrical activity of biceps femoris (P=0.001), semitendinosus (P=0.001), gluteus maximus (P=0.016) and erector spinae muscles (P=0.001). In the NHE group, although the activity of muscles increased by 13% in the biceps femoris, 11% in the Semitendinosus, 9% in the gluteus maximus and 4% in erector spinae muscles, the difference was significant only in the biceps femoris (P=0.001) and Semitendinosus (P=0.024). The results also showed a significant difference between the two groups in electrical activity of biceps femoris (P=0.021), semitendinosus (P=0.046) and erector spinae muscles (P=0.039). Conclusion Both standard and modified NHE are effective in preventing hamstring injury by increasing the electrical activity of the Biceps femoris and Semitendinosus, but the modified NHE is more effective in prevention of injury by changing the parameters of NHE and increasing the training load.